Myasthenia gravis - in pregnancy, during labor and in puerperium Myasthenia gravis - in der Schwangerschaft, unter der Geburt und im Wochenbett - Kühnert, Maritta; Kehl, Sven; Kuschel, B.; Schäfer-Graf, U.; Schmidt, M. (gynäkologische praxis, 2023)
Myasthenia gravis is an autoimmune disease with a variable spectrum of clinical presentations. It manifests as combination of weakness of ocular, bulbar, and respiratory muscle groups and muscles of the extremities. Young women of reproductive age are most commonly affected. The following items should be described and combined with appropriate recommendations: preconception planning, the impact of pregnancy, prepartum management, drug therapy in pregnancy, myasthenic and cholinergic crises, fetal monitoring, peripartum management including analgesia and anesthesia during labor and cesarean section as well as neonatal management and neonatal myasthenia gravis.
CRIS-Team Scopus Importer:2024-12-16
Keywords: labor; myasthenia gravis; myasthenic crisis; neonatal features; pregnancy